Pengaruh Kepemimpinan Manajerial, Leverage, Return On Asset Terhadap Kebijakan Dividen (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2016-2018) - Deby Nofianti Pratiwi; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis objectives of this research are: 1) To understand and analyze the influence of the Good Corporate Governance (GCG) towards the dividend policy in the manufacturing of the consumption goods sector. 2) To understand and analyze the influence of the Leverage (DER) towards dividend policy in the manufacturing of the consumption goods sector. 3) To understand and analyze the influence of the Return On Asset (ROA) towards dividend policy in the manufacturing of the consumption goods sector. The method used on this research is explanation. The data used are secondary data, obtained by documentation technique, which obtained by finding and collecting annual report data gained from websites. The object of this research are consumption goods manufacturing companies which are listed on the Indonesia Stock Exchange 2016-2018 periode, in the total 29 companies. The sampling selection used purposive sampling techniques, that in the end we got 15 companies.To solve the problem in this study, using the normality test, the classic assumption test, multiple linear regression test and hypothesis testing. The results of the data analysis show that: There is a significant positive effect on Leverage, Return On Assets on dividend policy in the Manufacturing companies in the goods and consumption sector while Good Corporate Governance has a significant negative effect on dividend policies in the goods and consumption sectors listed on the IDX.Key words: Good Corporate Governance, Leverage, Return On Asset, Dividend Policy.